A high-fat maternal diet decreases adiponectin receptor-1 expression in offspring. (January 2015) - Hou, Miao; Chu, Zhenyu; Liu, Ting; Lv, Haitao; Sun, Ling; Wang, Bo; Huang, Jie; Yan, Wenhua
Abstract In early life, over-nutrition may increase the risk of insulin resistance in the adult stage. Adiponectin and its receptor may play a key role in this process. This study aimed to identify the effect of a high-fat (HF) maternal diet on metabolic parameters and muscle adiponectin signaling in young adult offspring. We found that offspring born to dams fed HF chow (HF; 31% of calories from fat) had elevated body and adipose tissue weight and higher serum glucose levels after glucose challenge at three weeks (W3) and eight weeks (W8) of age. Offspring exposed to a HF diet also had higher serum adiponectin levels at W3 compared to controls. However, adiponectin levels were significantly decreased compared to controls by W8. Adiponectin receptor 1 mRNA expression in skeletal muscle was decreased in the HF group at W3 and W8, and there was no difference between the two groups in adiponectin receptor 2 expression. Furthermore, glucose transporter 4 mRNA and protein expression was decreased in the skeletal muscle of the HF group at W3 and W8. Our results suggest that a HF maternal diet decreases adiponectin receptor 1 expression in the offspring, which could contribute to reduced sensitivity to adiponectin and to adverse nutritional programing outcomes.